Effect of different TiO2 preparation techniques on the performance of the dielectric bolometer Ba06Sr0.4TiO3 as a distance sensor - Ibrahim, N.B; Yusrianto, E; Ibarahim, Z (Universiti Kebangsaan Malaysia, 2012)
In this study TiO2 films have been prepared using two different techniques i.e. sol-gel and electron gun evaporation (e-gun) techniques. The films were annealed at 300, 350 and 400oC in air. The microstructure study using field emission scanning electron microscopy and x-ray diffractometer showed nanometer grains size and only the film prepared by sol-gel and annealed at 400oC has anatase phase while others are amorphous. To study the effect of the films (as buffer layer) onto the dielectric bolometer Ba0.6Sr0.4TiO3 as distance sensor, sensors with the configuration of Al/BST/TiO2/RuO2/SiO2/Si were built. Two different measurements i.e. with and without infrared source were carried out to measure the sensitivity and repeatability of the sensors. The sensors which contained sol-gel TiO2 films gave reading for both type of measurements, indicating that the sensor can act as active and passive sensors. However, the sensors which contained e-gun TiO2 films only gave responses when the IR source was used, indicating that they can only act as passive sensors. The most sensitive sensor was TiO2 film prepared by sol gel and annealed at 350oC. In general sensors which contained TiO2 films prepared by sol gel showed good repeatability.